An ex vivo model for education and training of bilateral cleft lip surgery - Lutz, Rainer; Kesting, Marco Rainer; Weber, Manuel; Olmos, Manuel; Tasyürek, Deniz; Möst, Tobias; Bürstner, Jan; Schulz, Katja (BMC Medical Education, 2023)
Background: Bilateral cleft lip surgery is very challenging and requires a high level of skill, knowledge and experience. Existing high-fidelity simulation models that can be used by novice cleft surgeons to gain experience and expand their knowledge are rare and expensive. In this study, we developed a bilateral cleft lip model using porcine snout discs, which are available anywhere and inexpensive. Methods: Anatomic reference points of a patient with a bilateral cleft lip were superimposed with landmarks of the porcine snout disc on a foil template. The template was used to construct an ex vivo bilateral cleft lip model. Surgery was performed on the model according to Millard and the surgical steps were photodocumented analogous to two clinical cases of bilateral cleft lip surgery. The suitability of the model was further tested by twelve participants and evaluated using self-assessment questionnaires. Results: The bilateral cleft lip ex vivo model made of a porcine snout disc proved to be a suitable model with very low cost and ease of fabrication, as the template is reusable on any snout disc. The Millard procedure was successfully performed and the surgical steps of the lip plasty were simulated close to the clinical situation. Regarding the nasal reconstruction, the model lacks three-dimensionality. As a training model, it enhanced the participants comprehension of cleft surgery as well as their surgical skills. All participants rated the model as valuable for teaching and training. Conclusions: The porcine snout discs can be used as a useful ex vivo model for bilateral cleft lip surgery with limitations in the construction of the nose, which cannot be realistically performed with the model due to anatomical differences with humans. Benefits include a realistic tissue feel, the simulation of a multi-layered lip construction, a wide and rapid availability and low cost. This allows the model to be used by novice surgeons also in low-income countries. It is therefore useful as a training model for gaining experience, but also as a model for refining, testing and evaluating surgical techniques for bilateral lip plasty.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Bilateral cleft lip; Cadaver model; Cheiloplasty; Ex vivo model; Lip plasty; Porcine snout disc; Residency training; Skills lab; Surgical simulation; Teaching

An ex vivo model for education and training of unilateral cleft lip surgery. - Lutz, Rainer; Schulz, Katja; Weber, Manuel; Olmos, Manuel; Möst, Tobias; Bürstner, Jan; Kesting, Marco Rainer (BMC Medical Education, 2023)
BACKGROUND: Unilateral cleft lip surgery is a complex procedure, and the outcome depends highly on the surgeon's experience. Digital simulations and low-fidelity models seem inadequate for effective surgical education and training. There are only few realistic models for haptic simulation of cleft surgery, which are all based on synthetic materials that are costly and complex to produce. Hence, they are not fully available to train and educate surgical trainees. This study aims to develop an inexpensive, widely available, high-fidelity, ex vivo model of a unilateral cleft lip using a porcine snout disc. METHODS: A foil template was manufactured combining anatomical landmarks of the porcine snout disc and the anatomical situation of a child with a unilateral cleft. This template was used to create an ex vivo model of a unilateral cleft lip from the snout disc. Millard II technique was applied on the model to proof its suitability. The individual steps of the surgical cleft closure were photo-documented and three-dimensional scans of the model were analysed digitally. Sixteen surgical trainees were instructed to create a unilateral cleft model and perform a unilateral lip plasty. Their self-assessment was evaluated by means of a questionnaire. RESULTS: The porcine snout disc proved highly suitable to serve as a simulation model for unilateral cleft lip surgery. Millard II technique was successfully performed as we were able to perform all steps of unilateral cleft surgery, including muscle suturing. The developed foil-template is reusable on any porcine snout disc. The creation of the ex vivo model is simple and inexpensive. Self-assessment of the participants showed a strong increase in comprehension and an eagerness to use the model for surgical training. CONCLUSIONS: A porcine snout disc ex vivo model of unilateral cleft lips was developed successfully. It shows many advantages, including a haptic close to human tissue, multiple layers, low cost, and wide and rapid availability. It is therefore very suitable for teaching and training beginners in cleft surgery and subsequently improving surgical skills and knowledge. Further research is needed to finally assess the ex vivo model's value in different stages of the curriculum of surgical residency.
EVALuna2:567006

Developing an optimised method for accurate wear testing of dental materials using the ‘Rub&Roll’ device - Maier, Eva; Ruben, Jan; Palin, William M.; Bronkhorst, Ewald; Olmos, Manuel; Matta, Ragai; Loomans, Bas (Scientific Reports, 2024)
Dental materials are challenged by wear processes in the oral environment and should be evaluated in laboratory tests prior to clinical use. Many laboratory wear-testing devices are high-cost investments and not available for cross-centre comparisons. The ‘Rub&Roll’ wear machine enables controlled application of force, chemical and mechanical loading, but the initial design was not able to test against rigid antagonist materials. The current study aimed to probe the sensitivity of a new ‘Rub&Roll’ set-up by evaluating the effect of force and test solution parameters (deionized water; water + abrasive medium; acid + abrasive medium) on the wear behaviour of direct and indirect dental resin-based composites (RBCs) compared with human molars against 3D-printed rod antagonists. Molars exhibited greater height loss than RBCs in all test groups, with the largest differences recorded with acidic solutions. Direct RBCs showed significantly greater wear than indirect RBCs in the groups containing abrasive media. The acidic + abrasive medium did not result in increased wear of RBC materials. The developed method using the ‘Rub&Roll’ wear machine in the current investigation has provided a sensitive wear test method to allow initial screening of resin-based composite materials compared with extracted human molars under the influence of different mechanical and erosive challenges.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Abrasion; Dental materials; Erosion; Laboratory test method; Resin-based composites; Wear

Development of a porcine training model for microvascular fasciocutaneous free flap reconstruction - Nobis, Christopher-Philipp; Grottschreiber, Katharina; Olmos, Manuel; Möst, Tobias; Weber, Manuel; Kesting, Marco Rainer; Lutz, Rainer (Head & Face Medicine, 2024)
Background: In reconstructive surgery, improvements are needed in the effective teaching of free flap surgery. There is a need for easily accessible and widely available training without high financial costs or ethical concerns while still providing a realistic experience. Our aim was to develop an appropriate training model for microvascular flaps. Methods: We identified pig head halves as most appropriate regarding availability, cost, and realism. These accrue largely by the food industry, so no animals need to be sacrificed, making it more ethical from an animal welfare perspective. We evaluated the suitability as flap donor site and analyzed the vascular anatomy of 51 specimens. Results: Anatomical evaluation revealed a reliable and constant vascular anatomy, allowing the design of a flap model that can effectively illustrate the entire process of microvascular flap surgery. The process was divided into 6 key steps. The flap can be harvested after marking the vascular pedicle 5.3 cm from the lateral corner of the mouth. Skin island design and subsequent tissue dissection follow until a fasciocutaneous flap is raised, similar to a radial flap. Upon completion of flap harvesting, it can be freely transferred for defect reconstruction. Microvascular anastomosis can be performed on recipient vessels in the cervical region, and the difficulty can be individually adjusted. Conclusions: The developed training model is a reasonable compromise in terms of surgical realism, availability, didactic value, and cost/time effectiveness. We believe it is a powerful and effective tool with high potential for improving surgical education and training.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Free flap surgery; Microvascular flap; Oral and maxillofacial surgery; Plastic and reconstructive surgery; Porcine animal model; Surgical training model

Digital analysis of the human maxilla to enable semistandardized template tool reconstructions with free fibula transplants - Nobis, Christopher-Philipp; Kübler, Clara; Olmos, Manuel; Schulz, Katja; Glajzer, Jacek; Backhaus, Joy; Matta, Ragai; Kesting, Marco Rainer; Lutz, Rainer (Clinical Oral Investigations, 2024)
Objectives: This study analyzed the human maxilla to support the development of mean-value-based cutting guide systems for maxillary reconstruction, bridging the gap between freehand techniques and virtual surgical planning (VSP). Materials and methods: This retrospective cohort study used routine CT scans. DICOM data enabled 3D modelling and the maxilla was divided into four regions: paranasal (R1), facial maxillary sinus wall (R2), zygomatic bone (R3) and alveolar process (R4). Surface comparisons were made with a reference skull. Statistical analyses assessed anatomical variations, focusing on mean distance (Dmean), area of valid distance (AVD), integrated distance (ID) and integrated absolute distance (IAD). The study addressed hemimaxillectomy defects for two-segmental reconstructions using seven defined bilateral points to determine segmental distances and angles. Results: Data from 50 patients showed R2 as the most homogeneous and R4 as the most heterogeneous region. Significant age and gender differences were found in R3 and R4, with younger patients and females having more outliers. Cluster analysis indicated that males had R1 and R3 positioned anterior to the reference skull. The mean angle for segmental reconstruction was 131.24° ± 1.29°, with anterior segment length of 30.71 ± 0.57 mm and posterior length of 28.15 ± 0.86 mm. Conclusions: Anatomical analysis supported the development of semistandardized segmental resection approaches. Although gender and anatomical differences were noted, they did not significantly impact the feasibility of mean-value-based cutting-guide systems. Clinical relevance: This study provides essential anatomical data for creating cost-effective and efficient reconstruction options for maxillary defects, potentially improving surgical outcomes and expanding reconstructive possibilities beyond current techniques.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Digital morphology analysis; Fibula osteotomy; Head and neck anatomy; Maxillary reconstruction; Microvascular fibula transplant; Reconstructive surgery

Evaluation of a 3D printed training model with realistic spatial-anatomical conditions for head and neck microsurgery - Olmos, Manuel; Backhaus, Joy; Lutz, Rainer; Nobis, Christopher-Philipp; Koenig, Sarah; Kesting, Marco Rainer; Weber, Manuel (Clinical Oral Investigations, 2025)
Objectives: Although existing microsurgical models provide a high degree of realism in tissue properties, they often neglect the complex and constrained spatial-anatomical conditions typical of head and neck surgery. This study aims to evaluate the effectiveness of the Head and Neck Realistic Anatomical Condition Experience (RACE) model in enhancing microsurgical education. Methods: Using a microsurgical competency assessment tool and self-assessment questionnaires, the head and neck RACE model was evaluated through application in two student courses (10 participants) and one resident course (5 participants). In both groups, first the conventional chicken thigh model and then the RACE model were applied. Data were analyzed using a two-way repeated measures ANOVA with Welch’s statistics to assess differences between the groups. Results: In pregraduate courses, the transition from the conventional chicken thigh model to the RACE model initially led to a decline across all eight microsurgical performance parameters (Q1.1-Q4.2). However, after an additional day of training with the RACE model, all parameters—except tissue-preserving technique (Q1.2) — returned to or significantly exceeded baseline levels (Q1.2 p = 0.373, Q1.3 p = 0.003, Q2.1 p < 0.001, Q2.2 p = 0.022, Q2.3 p = 0.008, Q3.1 = 0.014, Q4.1 p = 0.036, Q4.2 p = 0.002). Conversely, residents showed immediate improvement in all parameters, except for suture distance to the vessel’s margin, upon switching to the RACE model. Conclusions: Head and neck RACE models provide a challenging and practical addition to microsurgery teaching. Clinical relevance: The positive impact on learning outcomes in this area supports the development of RACE models in other areas of microsurgical and general medical training, and therefore the education of students and clinical practitioners.
CRIS-Team Scopus Importer:2025-04-25
Keywords: 3D; Dentistry; Head and neck surgery; Microsurgery; Simulation; Teaching model

The interplay of stress and work-related musculoskeletal disorders in dental practitioners - Thies, Anke-Marei; Backhaus, Joy; Olmos, Manuel; Eitner, Stephan Frank (Quintessence International, 2024)
Objectives: Prevalence of work-related musculoskeletal disoring to their movement profile and the moderating effect of ders (WRMSDs) among general dental practitioners and orthostress on certain WRMSDs. Results: Three movement profiles dontists is approximated to range between 64% and 93%. Etiof general dental practitioners and orthodontists were signifiology of WRMSDs in the mentally and physically demanding cantly predictive of WRMSD. The minority could be character-occupation remains unclear, for which reason the aim of the ized as healthy (n = 45), whereas twice as many reported nearly study was to clarify the interplay of physical, psychological, twice as much pain (n = 90). Stress proved to be a strong, signif- and mental factors on WRMSDs. Method and materials: Of icant moderator of WRMSDs in relation to sex, employment 94 orthodontists and 187 general dental practitioners (mean status, and body mass index. Conclusion: The prevalence of age = 35 years) questioned using an online survey, 84% re-WRMSDs found was alarming. Given the feminization of den-ported persisting tension or pain in the back, neck, or shoultistry, and that being female, stressed, and an employee (rather ders. While 71% of females were employed (29% self-em-than self-employed) is a significant predictor of WRMSDs, this ployed), only 39% of male participants were employed. Cluster represents a danger to the German health system. analysis was used to characterize dental practitioners accord-(Quintessence Int 2024;55:756–765; doi: 10.3290/j.qi.b5687916)
CRIS-Team Scopus Importer:2025-02-04
Keywords: dental profession; employee; health; risk factors; stress; work-related musculoskeletal disorders